Phase Angle as a Predictor for Physical Function in Institutionalized Independent Older Adults - Morais, Ana (2022)
he aim of this study was to investigate the relationship between phase angle (PhA) and physical function in institutionalized, independent older adults. Physical function was evaluated using the Senior Fitness Test Battery. PhA was measured by electrical bioimpedance at 50 khz, and body composition parameters were also registered. Results showed that PhA significantly correlated with all physical fitness tests, except for arm curls. Regarding the results of the multivariate analysis, three models were created: Model 1, formed by a dependent variable "PhA" and two predictor variables "8 ft up-and-go" and "6 min walk"; Model 2, formed by a dependent variable "PhA" and three predictor variables "8 ft up-and-go", "6 min walk" and "30-s chair stand"; and Model 3, formed by a dependent variable "PhA" and four predictor variables "8 ft up-and-go", "6 min walk", "30-s chair stand" and "arm curl". Results showed that predictor variables had a significant influence on the PhA for all three models (Model 1: p = 0.001, 12.5%; Model 2: p = 0.002, 12.9%; and Model 3: p = 0.005, 13.1%). For women, Model 1 showed a significant influence of predictor variables on the PhA (p = 0.030, 9.3%). The results for men in Models 1, 2 and 3 showed significant influences on the PhA (p = 0.002, 31.2%; p = 0.006, 31.6%; and p = 0.016, 31.6%; respectively). This study confirmed previous studies regarding to the relationship between PhA and physical function. It also indicates that PhA could be an excellent predictor of physical function.